2019
DOI: 10.31219/osf.io/9x2yz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Income Diversification and Bank Efficiency in Vietnam

Abstract: Income Diversification and Bank Efficiency in Vietnam

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Still in this direction, diversification has proved to be a strategic practice within the scope of cooperative institutions. The more diversified, the better the efficiency scores tend to be, that is, an increase in diversification also represents an increase in cooperative efficiency, corroborating the findings of Sathye (2005) and Sang (2017), which also obtained a positive relationship between diversification and technical efficiency.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Still in this direction, diversification has proved to be a strategic practice within the scope of cooperative institutions. The more diversified, the better the efficiency scores tend to be, that is, an increase in diversification also represents an increase in cooperative efficiency, corroborating the findings of Sathye (2005) and Sang (2017), which also obtained a positive relationship between diversification and technical efficiency.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 80%
“…For Sang (2017), the relationship between bank efficiency diversification remains inconclusive. For Krakah and Ameyaw (2010), the services provided by financial institutions outside their traditional activities favor the performance of these institutions.…”
Section: Diversification (Div)mentioning
confidence: 99%
“…In line with the findings of Sufian ( 2009), Elyasiani and Wang (2012), Alhassan (2015) and Minh Sang (2017), positive and significant impact of bank intermediation function (measured by total loans and advances to total assets) on all computed efficiency parameters at 5 per cent significance level reveals effective use of assets for higher amount of credit creation.…”
Section: Efficiency Analysissupporting
confidence: 84%
“…They found that increased diversification improved bank efficiency but diversification benefits were offset by the increased exposure to volatile non-interest activities. A Vietnamese study by Minh Sang (2017) found that income diversification has positive impact on technical efficiency of 34 banks over the period 2007-2015. Using a sample of listed Chinese banks, Liang et al (2018) reported that income diversification improved accounting performance but decreased operating efficiency and market valuation because of diversification-induced agency cost.…”
Section: Empirical Literaturementioning
confidence: 99%
“…As listed banks gain more access to external finance source and customer base, their chance for the development of new banking services increase and thus, income diversification should also be higher. Some studies (Berger et al , 2010; Sang, 2017; Luu et al , 2019) found that income diversification of banks is positively associated with a bank’s performance. Therefore, income diversification could also be another channel for better performance of listed Vietnamese commercial banks.…”
Section: Results and Analysismentioning
confidence: 99%